2009
DOI: 10.1111/j.1365-2044.2009.06059.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the unprotected airway with a prototype Jaw‐Thrust‐Device – a prospective randomised cross‐over study

Abstract: SummaryDespite being a standard procedure during induction of anaesthesia, facemask ventilation can be a major challenge especially for inexperienced anaesthetists. We manufactured a Jaw-Thrust-Device designed to keep the patient's jaws in an optimised position, and thus to maintain the airway in a permanently patent state. Using a cross over design, we compared the influence of using the Esmarch manoeuvre (bimanual jaw-thrust), a nasopharyngeal airway, an oropharyngeal airway, or the Jaw-Thrust-Device on airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(16 reference statements)
3
3
0
Order By: Relevance
“…If the stomach is full of air, this can put pressure on the diaphragm and cause problems with ventilation. Research conducted on patients and on human corpses have confirmed the importance of reducing the frequency of ventilation and inspiratory pressure so as to minimize the risk of blowing air into the stomach during positive pressure ventilation in patients with unprotected airways [5, 3133]. Our research showed that the percentage of artificial breaths where air found its way into the stomach did not differ significantly in both methods ( p > 0.05).…”
Section: Discussionsupporting
confidence: 58%
“…If the stomach is full of air, this can put pressure on the diaphragm and cause problems with ventilation. Research conducted on patients and on human corpses have confirmed the importance of reducing the frequency of ventilation and inspiratory pressure so as to minimize the risk of blowing air into the stomach during positive pressure ventilation in patients with unprotected airways [5, 3133]. Our research showed that the percentage of artificial breaths where air found its way into the stomach did not differ significantly in both methods ( p > 0.05).…”
Section: Discussionsupporting
confidence: 58%
“…If the stomach is full of air, this can put pressure on the diaphragm and cause problems with ventilation. Studies by numerous authors have confirmed the importance of reducing the frequency of ventilation and inspiratory pressure so as to minimize the risk of blowing air into the stomach during positive pressure ventilation in patients with unprotected airways [5,[31][32][33]. Our research showed that the percentage of artificial breaths where air found its way into the stomach did not differ significantly in both methods (p>0.05).…”
Section: Discussionsupporting
confidence: 58%
“…If the stomach is full of air, this can put pressure on the diaphragm and cause problems with ventilation. Research conducted on patients and on human corpses have confirmed the importance of reducing the frequency of ventilation and inspiratory pressure so as to minimize the risk of blowing air into the stomach during positive pressure ventilation in patients with unprotected airways [5,[31][32][33]. Our research showed that the percentage of artificial breaths where air found its way into the stomach did not differ significantly in both methods (p > 0.05).…”
Section: Discussionsupporting
confidence: 56%